腹水の有無に着目した拘扼性イレウスの早期診断法 - 吉川 健治; 外山 和隆; 戸口 啓介; 山口 拓也; 平林 邦昭 (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2011)
The relationship between the appearance of ascites and the degree of intestinal ischemia in strangulated obstruction has not been studied in detailed. The aim of this study is to elucidate the relationship between the appearance of ascites and degree of intestinal ischemia. METHOD: The subjects were 20 patients with strangulated intestinal obstruction who underwent laparotomy in our hospital. They were divided into two groups: those with intestinal necrosis (n=6); and those without (n=14). The patients were compared for frequency of ascites, systemic inflammatory response syndrome (SIRS) factors, and the serum levels of CRP, LDH and CPK. RESULTS: SIRS factors and the serum levels of CRP, LDH and CPK were not significantly associated with the presence of intestinal necrosis. Eighteen patients presented with ascites. Of the 14 patients without intestinal necrosis, 12 presented with ascites. On the other hand, all 5 patients who presented with strangulated intestinal obstruction were positive for SIRS. CONCLUSIONS: In strangulated intestinal obstruction, the appearance of ascites could be identified before the increase in SIRS factors and other serological parameters. Thus, the appearance of ascites may have a potential role in contributing to the diagnoses of early stages of intestinal ischemia in patients with strangulated obstruction. 絞扼性イレウスでは，高率に腹水が出現する。今回，絞扼性イレウスにおける腹水が腸管虚血がどの程度進行した段階で生じるのかを明らかにする。対象と方法：緊急開腹手術が施行された絞扼性イレウス20例を6例の壊死群，14例の非壊死群に分け，以下の項目を比較検討した。1．両群の初診時の腹水の出現率　2．SIRS陽性率　3．血液生化学的検査値（CRP，PK，LDH）異常の出現率。結果：SIRS陽性率，血液生化学的検査値の異常値出現率のいずれも壊死群，非壊死群で有意差は認めなかった。SIRS陽性率は壊死群33％ 非壊死例21％であった。一方，腹水出現率は壊死群100％，非壊死群で86％であった。結語：絞扼性イレウスにおける腹水の出現は，腸管壊死前でさらにSIRS項目，血液生化学的異常値が出現する以前に出現すると考えられる。